Minimally invasive approach of chronic pleural empyema using uniportal video-assisted thoracoscopy and intracavitary vacuum system (ICVS) - Ruiz, Claudio A.; Aranibar, José R.; Otero, Walter G.; Giacoia, Alejandro; Gloazzo, Emiliano A. (Revista Argentina de Cirugía, 2026)
Background: The number of patients with pleural empyema has increased in recent years. Despite antibiotic therapy and the minimally invasive procedures currently available, management of pleural empyema has high morbidity and mortality. Objective: The aim of this study was to describe the results of the management of patients with chronic pleural empyema using uniportal video-assisted thoracoscopy and intracavitary vacuum systems (ICVS). Material and methods: We conducted a retrospective, observational and descriptive study using data obtained from the medical records of patients with diagnosis of chronic pleural empyema treated between August 2023 and February 2024. Results: A total of 13 patients with chronic pleural empyema were treated; mean age was 66 years (range 39-80), and 8 were male. Eight patients presented with dyspnea, 9 with chest pain and 13 had fever. Mean time from the onset of symptoms was 37 days (range 25-60). All the patients underwent ultrasound-guided thoracocentesis, uniportal video-assisted thoracoscopy, and pleural lavage. The visceral peel was opened and the ICVS was constructed in all the cases. The infection was resolved in all the cases and closure of the empyematic cavity was achieved in 10 patients (76.9%) at discharge. Conclusion: This experience showed that the minimally invasive procedure was effective even in patients at high surgical risk, positioning it as a first-line surgical option for the management of chronic pleural empyema.